Legenda Tokoh Jokotole sebagai Representsi Pendidikan Karakter dalam Pengembangan Media Aplikasi Android pada Pembelajaran Bahasa Indonesia Aspek Kemampuan Membaca Kelas VII Di SMP Negeri se-Kabupaten Bangkalan - Ahmad Jami'ul Amil; Arief Setyawan; Prita Dellia (Proceedings of The ICECRS, 2019)
These studies are research on the development of research and development (R & D) using the Borg and Gall model. However, this development research takes several stages, namely, problem identification, information gathering, product design, and product testing. The results of the study found that Jokotole figures were legendary figures in the Madura region from Bangkalan, Sampang, Pamekasan, and Sumenep. The legend of Jokotole is found in every legend in the villages of Madura, there are 38 stories that tell the character of Jokotole both in his journey (stop) so as to create his own legend or narrate the battle against his enemies, while in the Bangkalan region there are 12 legends which tell Jokotole namely in the area of talk, keleyen, tip plate, and so forth. In this development research, the Jokotole story was made the main character in its emergence as a learning media based on andorid, because the tendency of the majority of Madurese people to accept Jokotole figures as positive figures starting from Jokotole's birth, journey, chivalry, spirituality, and death. Furthermore, in the development research this took the legend of the villages that gave rise to the character of Jokotole. Andorid media based on learning media applications ranging from stories, places (the area adopted from google map maps, questions, and reading ability tests using the ability formula to read elementary school children, namely junior high school. Jokotole figures in the andorid learning media application created using multimedia unity and design Corel Draw with Story Board Jokotole character journey when visiting the western Madura area until the trip in Bangkalan area, namely in the village of Telang, Socah, Ujung Plate, Bancaran, and Jambu Village.